Sebaceous carcinoma in situ as a concept and diagnostic entity - Miglena K. Komforti (Mattioli1885, 2017)
Although carcinoma in situ has been accepted as a well-established concept and diagnostic category, for reasons unknown sebaceous carcinoma in situ has not been recognized yet in general pathology or dermatopathology. Such lesions have always been misinterpreted as either benign neoplasm or sebaceous carcinoma. In the present essay, we provide a convincing account supporting sebaceous carcinoma in situ as a valid concept and diagnostic entity via critical literature review and histopathological assessment and illustration. Recognizing sebaceous carcinoma in situ as a valid concept and diagnostic entity will certainly help to avoid misinterpretation and subsequently under or over treatment of such lesions.